2018
DOI: 10.3847/1538-3881/aad781
|View full text |Cite
|
Sign up to set email alerts
|

Ground- and Space-based Detection of the Thermal Emission Spectrum of the Transiting Hot Jupiter KELT-2Ab

Abstract: We describe the detection of water vapor in the atmosphere of the transiting hot Jupiter KELT-2Ab by treating the star-planet system as a spectroscopic binary with high-resolution, ground-based spectroscopy. We resolve the signal of the planet's motion with deep combined flux observations of the star and the planet. In total, six epochs of Keck NIRSPEC L-band observations were obtained, and the full data set was subjected to a cross correlation analysis with a grid of self-consistent atmospheric models. We mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 56 publications
1
76
0
Order By: Relevance
“…it is a two-dimensional cross correlation with the stellar coefficients dominating the planet coefficients by orders of magnitude. The mapping of Lockwood et al (2014) was also recently adopted in Piskorz et al (2018) to combine Keck NIRSPEC K-band data with Spitzer for the transiting hot-Jupiter Kelt-2 Ab. However, we again stress that such formalism cannot be applied to our data analysis where we make use of the change in planet radial velocity with time.…”
Section: Mappingsmentioning
confidence: 99%
“…it is a two-dimensional cross correlation with the stellar coefficients dominating the planet coefficients by orders of magnitude. The mapping of Lockwood et al (2014) was also recently adopted in Piskorz et al (2018) to combine Keck NIRSPEC K-band data with Spitzer for the transiting hot-Jupiter Kelt-2 Ab. However, we again stress that such formalism cannot be applied to our data analysis where we make use of the change in planet radial velocity with time.…”
Section: Mappingsmentioning
confidence: 99%
“…The median TP profile is shown in black, with 1σ and 2σ confidence intervals outlined in red. Overlaid on top of the retrieval results are radiative-convective equilibrium profiles (blue) derived using the ScCHIMERA modeling tool described in Piskorz et al (2018) and Bonnefoy et al (2018), generated using the T eff and log(g) range derived from the retrieval results. We compute the effective temperature as in Parts I and II by numerically integrating for the bolometric flux of the retrieved spectral spread for each object from 1 -20 µm.…”
Section: Vertical Temperature Structurementioning
confidence: 99%
“…Figure 5 summarizes these trends (red, yellow points) in comparison to predictions from a self-consistent grid model (black curves) and to those derived for the warmer T-dwarfs from Part II (blue points). Our chosen grid model was introduced and validated in Piskorz et al (2018) and Bonnefoy et al (2018). We produce a grid of models given T eff , log(g), metallicity, and assume radiative-convective thermochemical equilibrium.…”
Section: Chemical Trendsmentioning
confidence: 99%
“…Previous multi-epoch detection works (e.g., Piskorz et al 2018) have reported significance by comparing the likelihood of a Gaussian fit (representing a detection) versus a linear fit (representing a non-detection) to the peak. This method has given significances of hot Jupiter detections in the range of 3-4σ.…”
Section: Planet Mass and Orbital Solutionmentioning
confidence: 99%
“…These direct detection techniques work by treating a star/planet system as a spectroscopic binary and measuring the radial velocity signature of the planet. This signature will have an opposite phase to the stellar radial velocity curve (see Figure 1), and by combining its amplitude, which we call K p , the planetary Keplerian line-of-sight velocity, with the stellar radial velocity amplitude K, we can break the mass/inclination degeneracy left by the stellar radial velocity technique and further characterize the planet's atmosphere (e.g., Brogi et al 2012Brogi et al , 2013Brogi et al , 2014Lockwood et al 2014;Piskorz et al 2016Piskorz et al , 2017Birkby et al 2017;Piskorz et al 2018). These techniques have been used to detect the presence of H 2 O (e.g., Birkby et al 2017), CO (e.g., Brogi et al 2012), TiO (Nugroho et al 2017), HCN (e.g., Hawker et al 2018), and CH 4 (Guilluy et al 2019) in planetary atmospheres, as well as winds (Snellen et al 2010) and planetary rotation rate (Brogi et al 2016).…”
Section: Introductionmentioning
confidence: 99%